PMA and crystal‐induced neutrophil extracellular trap formation involves RIPK1‐RIPK3‐MLKL signaling. Issue 1 (30th November 2015) - Desai, Jyaysi; Kumar, Santhosh V.; Mulay, Shrikant R.; Konrad, Lukas; Romoli, Simone; Schauer, Christine; Herrmann, Martin; Bilyy, Rostyslav; Müller, Susanna; Popper, Bastian; Nakazawa, Daigo; Weidenbusch, Marc; et al.
Abstract : Neutrophil extracellular trap (NET) formation contributes to gout, autoimmune vasculitis, thrombosis, and atherosclerosis. The outside‐in signaling pathway triggering NET formation is unknown. Here, we show that the receptor‐interacting protein kinase (RIPK)‐1‐stabilizers necrostatin‐1 or necrostatin‐1s and the mixed lineage kinase domain‐like (MLKL)‐inhibitor necrosulfonamide prevent monosodium urate (MSU) crystal‐ or PMA‐induced NET formation in human and mouse neutrophils. These compounds do not affect PMA‐ or urate crystal‐induced production of ROS. Moreover, neutrophils of chronic granulomatous disease patients are shown to lack PMA‐induced MLKL phosphorylation. Genetic deficiency of RIPK3 in mice prevents MSU crystal‐induced NET formation in vitro and in vivo. Thus, neutrophil death and NET formation may involve the signaling pathway defining necroptosis downstream of ROS production. These data imply that RIPK1, RIPK3, and MLKL could represent molecular targets in gout or other crystallopathies.